Unveiling the role of tRNA-derived small RNAs in MAPK signaling pathway: implications for cancer and beyond - Wang, Qurui; Huang, Qinyuan; Ying, Xiaowei; Shen, Jinze; Duan, Shiwei (Frontiers in Genetics, 2024)
tRNA-derived small RNAs (tsRNAs) are novel small non-coding RNAs originating from mature or precursor tRNAs (pre-tRNA), typically spanning 14 to 30 nt. The Mitogen-activated protein kinases (MAPK) pathway orchestrates cellular responses, influencing proliferation, differentiation, apoptosis, and transformation. tsRNAs influence the expression of the MAPK signaling pathway by targeting specific proteins within the pathway. Presently, four MAPK-linked tsRNAs have implications in gastric cancer (GC) and high-grade serous ovarian cancer (HGSOC). Notably, tRF-Glu-TTC-027 and tRF-Val-CAC-016 modulate MAPK-related protein expression, encompassing p38, Myc, ERK, CyclinD1, CyclinB, and c-Myc, hindering GC progression via MAPK pathway inhibition. Moreover, tRF-24-V29K9UV3IU and tRF-03357 remain unexplored in specific mechanisms. KEGG analysis posits varied tsRNAs in MAPK pathway modulation for diverse non-cancer maladies. Notably, high tRF-36-F900BY4D84KRIME and tRF-23-87R8WP9IY expression relates to varicose vein (VV) risk. Elevated tiRNA-Gly-GCC-001, tRF-Gly-GCC-012, tRF-Gly-GCC-013, and tRF-Gly-GCC-016 target spinal cord injury (SCI)-related brain-derived neurotrophic factor (BDNF), influencing MAPK expression. tRF-Gly-CCC-039 associates with diabetes foot sustained healing, while tRF-5014a inhibits autophagy-linked ATG5 in diabetic cardiomyopathy (DCM). Additionally, tsRNA-14783 influences keloid formation by regulating M2 macrophage polarization.Up-regulation of tRF-Arg-ACG-007 and down-regulation of tRF-Ser-GCT-008 are associated with diabetes. tsRNA-04002 alleviates Intervertebral disk degeneration (IDD) by targeting PRKCA. tsRNA-21109 alleviates Systemic lupus erythematosus (SLE) by inhibiting macrophage M1 polarization. The up-regulated tiNA-Gly-GCC-002 and the down-regulated tRF-Ala-AGC-010, tRF-Gln-CTG-005 and tRF-Leu-AAG-001 may be involved in the pathogenesis of Lupus nephritis (LN) by affecting the expression of MAPK pathway. Downregulation of tsRNA-1018, tsRNA-3045b, tsRNA-5021a and tsRNA-1020 affected the expression of MAPK pathway, thereby improving Acute lung injury (ALI). This review comprehensively dissects tsRNA roles in MAPK signaling across cancers and other diseases, illuminating a novel avenue for translational medical exploration.